A Gamification-based Social Collaborative Architecture to increase resilience against natural disasters - Horita, Flávio E. A.; Assis, Luiz F. F. G.; Castanhari, Raul E. S.; Isotani, Seiji; Cruz, Wilmax M.; de Albuquerque, João Porto (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2014: Anais do X Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2014.6131, 2014)
Natural disasters have led to the need for urgent measures to mitigate the effects of these accidents. The question of awareness is extremely important in dealing with disasters, and collaborative systems are very serviceable for this. In this context, the aim of this work is to outline a gamification-based social collaborative architecture (GSCA) to increase resilience against natural disasters. We have combined techniques to produce and share information through the interaction of a large number of people, such as those employed in social media and serious games. This architecturewas evaluated and analyzed using the Voluntary in Action, a web platform which applies the components defined in the GSCA. The results suggest that gamification is a system with a great potential to help increase the knowledge of a community about disasters.